Factors modulating post-activation potentiation of jump, sprint, throw, and upper-body ballistic performances: A systematic review with meta-analysis - Seitz, L. B.; Haff, G. (Sports Medicine, 2016)
Background: Although post-activation potentiation (PAP) has been extensively examined following the completion of a conditioning activity (CA), the precise effects on subsequent jump, sprint, throw, and upper-body ballistic performances and the factors modulating these effects have yet to be determined. Moreover, weaker and stronger individuals seem to exhibit different PAP responses; however, how they respond to the different components of a strength-power-potentiation complex remains to be elucidated.